Relevance of social capital in womens business performance in Bangladesh (Journal of the Bangladesh Agricultural University, 2017)
Social capital has been projected as a key resource in entrepreneurial success. While the association between successful business activity by rural women and their ability in building social capital is often seen as a pathway of poverty reduction, a thorough understanding of the relevance of social capital in womens business performance could have crucial insights into ways for alleviating rural poverty in developing countries. Nonetheless, the relevance of social capital in womens business performance has hardly studied in the specific context of Bangladesh. The present review is undertaken to fill this information gap. Social capital has positive impact on gaining legitimacy, building mutual trust and co-operation in womens business. Besides, women enterprises with enhanced social capital are found to possess better access to other forms of capital. The review shows the importance of external actors such as microfinance institutions in developing social capital of women enterprises in Bangladesh. Alongside microfinance, regulative factors such as different rules and regulations of the government can positively facilitate women entrepreneurship development in rural Bangladesh.J. Bangladesh Agril. Univ. 15(1): 87-94, January 2017